2010
DOI: 10.1136/jnnp.2009.201129
|View full text |Cite
|
Sign up to set email alerts
|

Pallidal neuronal discharge in Parkinson's disease following intraputamenal fetal mesencephalic allograft

Abstract: Analysis of firing rate, bursting discharge and oscillatory activity showed that the graft corrected some, but not all, of the abnormalities associated with the off-medication state. Additionally, in the transplanted patient, voluntary hand movement produced a marked reduction in pallidal discharge rate at multiple GPi recording sites, which was not observed during active movement in other patients. These findings are consistent with a persistent effect of transplanted dopamine cells on basal ganglia outflow a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 39 publications
2
5
0
Order By: Relevance
“…Interestingly, in the same study, patients subsequently developed dyskinesias, suggesting that soon after infusion, a “normal” firing rate in the STN was achieved, relieving parkinsonian symptoms, but later firing rates were further depressed, producing hyperkinesias. In the case of dyskinesias associated with grafting of fetal midbrain neurons, lower firing rates, as well as bursting, were observed in the GPi (Richardson et al 2011), also supporting the Rate Model.…”
Section: Introductionsupporting
confidence: 62%
“…Interestingly, in the same study, patients subsequently developed dyskinesias, suggesting that soon after infusion, a “normal” firing rate in the STN was achieved, relieving parkinsonian symptoms, but later firing rates were further depressed, producing hyperkinesias. In the case of dyskinesias associated with grafting of fetal midbrain neurons, lower firing rates, as well as bursting, were observed in the GPi (Richardson et al 2011), also supporting the Rate Model.…”
Section: Introductionsupporting
confidence: 62%
“…The clinical guidelines presented in this document apply more to mature/functionally differentiated cell therapy. To date, clinical trials of treatments based on those categories of cells have been carried out in over 40 countries with documented safety and functional neurological improvement for patients with CNS diseases and damage 74 114 .…”
Section: Introductionmentioning
confidence: 99%
“…Some refractory cases of graft-induced dyskinesia have been treated with DBS. Intraoperative recording during these DBS implantation surgeries has indicated that similar to levodopa-induced dyskinesia, graft-induced dyskinesia is associated with overactivity of neurons in the direct striatal pathway [104].…”
Section: Other Surgical Therapies: Lesions Deep Brain Stimulation and mentioning
confidence: 99%